Post-induction Measurable Residual Disease Using Multicolor Flow Cytometry Is Strongly Predictive of Inferior Clinical Outcome in the Real-Life Management of Childhood T-Cell Acute Lymphoblastic Leukemia: A Study of 256 Patients - Tembhare, Prashant R.; Narula, Gaurav; Khanka, Twinkle; Ghogale, Sitaram; Chatterjee, Gaurav; Patkar, Nikhil V.; Prasad, Maya; Badrinath, Yajamanam; Deshpande, Nilesh; Gudapati, Pratyusha; Verma, Shefali; Sanyal, Mahima; et al. (Frontiers in Oncology, 2020)
Background: Measurable/minimal residual disease (MRD) status is suggested as a powerful indicator of clinical-outcome in T-cell lymphoblastic leukemia/lymphoma (T-ALL). Contrary to B-cell ALL, reports on T-ALL MRD are limited and mostly based on molecular methods, mainly from developed countries. Multicolor flow cytometry (MFC)-based T-ALL studies are very few. Clinically relevant cut-off levels and ideal time-point for MRD assessment are still inconclusive. In view of lack of T-ALL MRD data from the developing world, we evaluated the prognostic value of MFC-based post-induction (PI)-MRD assessment in T-ALL in the context of standard practice. Methods: We included 256 childhood-T-ALL patients (age<15 years) treated with a modified-MCP841 protocol, which uses high-dose cytarabine during consolidation, as a part of standard hospital practice. MRD was studied using 10-color 11-antibody MFC with any level of detectable disease being considered positive. Post-induction (PI)-MRD was available in all patients, and post-consolidation (PC) MRD was available mostly in PI-MRD-positive patients (n=90). Results: Three years cumulative-incidence-of-relapse (3years-CIR) in PI-MRD-positive patients was inferior to negative patients (46.3% versus 18.4%). The median relapse-free-survival (RFS), event-free-survival (EFS) and overall-survival (OS) with hazard ratio (HR) of PI-MRD-positive patients were 21.4 months vs not reached (p<0.0001, HR-4.7), 21.6 months vs. not-reached (p=0.0003, HR-2.01) and 37.3 months vs not reached (p=0.026, HR-1.64) respectively. RFS, EFS and OS of patients with PI-MRD<0.01% (n=17) were as inferior as PI-MRD≥0.01% in comparison with MRD-negative patients with HR of 4.7 (p<0.0001), 2.45 (p=0.0003) and 2.5 (p=0.029) respectively. Three-years-CIR of patients with hyperleukocytosis (≥100 x 109/L) was also higher (50.5% vs. 27.6%) with inferior RFS, EFS, and OS. Among PI-MRD-positive patients, 3years-CIR, RFS, EFS, and OS of PC-MRD-positive were also inferior to that of negative patients. On multivariate analysis any-level detectable PI-MRD and hyperleukocytosis remained independently associated with inferior RFS, EFS, and OS. A combination of PI-MRD-positive status and hyperleukocytosis identified the patients with the worst clinical outcomes. Conclusion: Detectable PI-MRD using MFC was found to be the strong predictive factor of inferior clinical outcome in T-ALL patients. The combination of PI-MRD status and hyperleukocytosis provides the most influential tool for the management of T-ALL in resource constrained settings from developing world.